Multidimensional evaluation of quality differences for Dendrobium officinale stems grown under different cultivation environments based on widely targeted metabolomics, network pharmacology, molecular docking, and cell experiments - Hou, Yingyue; Du, Guangying; Li, Jing; Liu, Pei; Zhang, Jinqiang (Frontiers in Plant Science, 2025)
IntroductionDendrobium officinale is an endangered perennial epiphytic herbaceous plant. In the Chinese Pharmacopoeia, the dried stems of D. officinale are used medicinally and are commonly utilized as a medicinal and food homologous product. Notable variations in the quality of D. officinale stems are observed across different cultivation environments; however, the underlying mechanisms remain unclear.MethodsMetabolites in D. officinale stems grown in stone epiphytic, tree epiphytic, and greenhouse environments were identified using UPLC-MS/MS-based widely targeted metabolomics. Differential metabolites from stems grown in different cultivation environments were selected for studies on quality differences. Network pharmacology was employed to investigate the core targets of these differential metabolites, and molecular docking validation was conducted with these metabolites to identify quality markers. Finally, a combination of network pharmacology and in vitro experimental results was used to explore the reasons behind the differences in therapeutic effects of D. officinale stems grown in various cultivation environments.ResultsA total of 1929 primary and secondary metabolites were identified. Compared to the tree epiphytic and greenhouse environments, 58 primary and secondary metabolites were up-regulated in the stone epiphytic environment. Among these, 7 amino acids and their derivatives were exclusively found as up-regulated primary metabolites, while 18 flavonoids constituted the main up-regulated secondary metabolites. The binding affinities of the 18 flavonoids to the core targets (MAOA and TNF) were superior to those of other up-regulated metabolites, and they can be utilized in quality difference studies, particularly nicotiflorin and isoquercitrin. Stems grown in the stone epiphytic environment showed a superior protective effect on chronic atrophic gastritis cells compared to the other two environments. This was associated with increased binding of differential metabolites to targets such as MAOA and TNF and decreased binding to targets such as SRC and PTGS2.DiscussionThe composition and content of metabolites in D. officinale stems are influenced by the cultivation environment, which in turn affects the therapeutic effects of the stems. The change of the target preference could be the reason for the difference in drug efficacy. This study introduces a novel approach for distinguishing the quality of D. officinale stems grown under different cultivation environments and exploring the variations in their therapeutic effects.